Model systems, lipid rafts, and cell membranes - Simons, Kai (2004)
Views of how cell membranes are organized are presently changing. The lipid bilayer that constitutes these membranes is no longer understood to be a homogeneous fluid. Instead, lipid assemblies, termed rafts, have been introduced to provide fluid platforms that segregate membrane components and dynamically compartmentalize membranes. These assemblies are thought to be composed mainly of sphingolipids and cholesterol in the outer leaflet, somehow connected to domains of unknown composition in the inner leaflet. Specific classes of proteins are associated with the rafts. This review critically analyzes what is known of phase behavior and liquid-liquid immiscibility in model systems and compares these data with what is known of domain formation in cell membranes.